The Influence of Mutual Service Culture on Organizational Productivity Through Leadership Style at The National Narcotics Agency of The Province East Kalimantan - Rudi Hartono; Kemal Taufik; Sri Wahyuningsih (Dinasti Publisher, 2026)
The purpose of this study is to analyze the influence of a culture of mutual service on organizational productivity, analyze the influence of leadership style on organizational productivity, analyze the influence of a culture of mutual service and leadership style on organizational productivity, and analyze the influence of a culture of mutual service on organizational productivity through leadership style at the East Kalimantan Provincial Narcotics Agency (BNNP) The regression analysis results showed a t-value of 6.905 with a significance level of 0.000 (<0.05). A culture of mutual service has a positive and significant effect on leadership style at the BNNP in East Kalimantan. The test results showed a regression coefficient of 0.792 with a significance level of 0.000 (<0.05). Leadership style has a positive and significant effect on organizational productivity at the BNNP in East Kalimantan. The analysis results showed a t-value of 2.117 with a significance level of 0.037 (<0.05). Leadership style partially mediates the effect of a culture of mutual service on organizational productivity. The Sobel test results indicate a significant indirect effect of a culture of mutual service on organizational productivity through leadership style.